Contemporary Clinical Practice The Holding Environment Under Assault - Ruderman, Ellen; Tosone, Carol; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Ongoing wars, a sinking economy, growing inequities$1 (Bmore than ever, the outside world leaves a large footprint on patients$1 (Bpsyches. Not surprisingly, therapists are experiencing increased tension between sociopolitical realities, the inner world of the treatment hour, and their own anxieties, training, and ethics. How does one maintain trust and authenticity? Should the concept of therapeutic neutrality still apply at a time of widespread societal trauma and grief? The contributors to Contemporary Clinical Practice have grappled with these and related questions, and offer stimulating answers. Beginning with its subtitle, The Holding Environment under Assault, the book gauges the extent to which modern life impinges on the therapeutic relationship, and offers steps for clinicians to reconcile these inner and outer worlds in practice and find healing for themselves as well as their clients. Skillful analysis and illustrative case examples bring modern perspective to existential dilemmas common in therapy, from transference, countertransference, and boundary difficulties to challenges posed by new technology. Thought-inspiring topics include: Integrating the interior and exterior worlds of clinical social work. Grief and loss in an age of global trauma. Virtual intimacy: help or hindrance? Considerations for psychoanalytic treatment in time of war. What happens to confidentiality when the government enters the treatment room? The loss of dissidence in psychoanalysis. An owner$1 (Bs manual to 21st-century therapy, Contemporary Clinical Practice: The Holding Environment under Assault will be hailed by social work professionals, counselors, and policymakers as provocative, sobering, and ultimately career-affirming.s
Introduction: The World Outside and its Impact on the Treatment Process -- Shared Trauma and Self-Disclosure in the Therapeutic Process -- The Erosion of the Socio-Political Holding Environment and Potential Space for Creative Repair in Treatment -- Grief and Loss in an Age of Global Trauma: Protest and Despair vs. Attachment and Reorganization -- Integrating the Internal and External Worlds of Clinical Social Work -- What Happens to Confidentiality When the Government Enters the Treatment Room via the Patriot Act, HIPPA, and Managed Care? -- The Influence of Outside Forces on Social Work Education -- Real Experiences Revisited: The Significance of Attachment, Separation, and Loss in Clinical Social Work Treatment -- Psychoanalysis and Social Critique -- Considerations for Psychoanalytic Treatment in a Time of War.
Keywords: Social sciences; Social policy; Social work; Psychology, clinical; Applied psychology; Social Sciences; Social Work; Psychotherapy and Counseling; Social Policy; Clinical Psychology